Sun-bathing by Montagu’s Harrier Circus pygargus on its African wintering grounds - Villers, Alexandre; Gangloff, Benoit; Turpaud-Fizzala, Victor; Augiron, Steve (Biodiversity Observations, 2014)
shortly after landing on the shore, walked away from the water and spread its wings and tail in unusual manner... Similarly, researchers extremely experienced with this species...could not recall observing similar behaviour on the species breeding grounds...